The effectiveness of teaching emotion-based processing strategies on academic stress, social adjustment and psychological distress of high school male students - kianoosh beyranvand; naser behroozi; manijeh shehni yailagh; gholamhosein Maktabi (مجله علوم روانشناختی)
Background: Studies have shown that the experience of emotions in educational environments affects academic stress, social adjustment and psychological distress. The basic experiential processing method under the title of emotion-oriented processes leads to the activation and reorganization of emotional schemas. The review of related research literature shows that limited studies have investigated the teaching of emotional processing strategies on academic stress, social adjustment and psychological distress of students. Aims: This research was conducted with the aim of determining the effectiveness of emotional processing strategies training on academic stress, social adjustment and psychological distress in male second year high school students. Methods: The design of the current research was experimental, of pre-test-post-test type with a control group. The statistical population of the research included all male students of the second year of high school in Khorram Abad who were studying in the academic year of 2001-2001. Using multi-stage random sampling method, 60 students were selected and randomly placed in two experimental and control groups. The experimental group underwent an 8-session educational intervention of emotion-oriented processing strategies (Gross, 2007). In this research, the scales of academic stress of Zajakova et al. (2005), Sinha and Singh (1993) social adjustment and Kessler (2003) psychological distress were used and analysis of covariance was used to analyze the data. Results: The findings of the research showed that teaching emotion-oriented processing strategies reduces academic stress, increases social adaptation, and reduces psychological distress in second year high school male students at a significance level of p< 0.01. Conclusion: According to the findings, it is concluded that emotion-oriented processing training can help reduce academic stress and psychological distress, and increase the level of social adjustment of second year male students. Therefore, paying attention to teaching emotion-oriented processing strategies can play an important role in improving the academic, psychological and social status of students in school.